2014
DOI: 10.1097/paf.0000000000000064
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death Due to Hydatid Cyst

Abstract: The natural history of the echinococcosis can be studded with multiple complications; the most formidable is sudden death. We studied the epidemiological, pathological, and thanatological features of 34 sudden deaths due to hydatid cyst. The mean age was 33.2 years. A male predominance was observed with a sex ratio of 1.8. Most of our victims were from rural areas (79.4%). Sudden death was preceded by prodromal symptoms in 61.7% of cases. The most common was dyspnea (23.5%), followed by hemoptysis (11.8%). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
12
1
Order By: Relevance
“…We have detected a higher incidence among the rural population, but the results of the investigations conducted by Chaâbane-Banaoues et al [ 16 ] have shown that the pathogen dissemination is influenced by human activities and behavior towards the infected viscera. Our results don’t show male predominance among the 19 deaths in contrast to the studies of some other authors [ 17 , 18 ], who have described the male predominance of mean age 31–33.2 years in their works.…”
Section: Discussioncontrasting
confidence: 99%
“…We have detected a higher incidence among the rural population, but the results of the investigations conducted by Chaâbane-Banaoues et al [ 16 ] have shown that the pathogen dissemination is influenced by human activities and behavior towards the infected viscera. Our results don’t show male predominance among the 19 deaths in contrast to the studies of some other authors [ 17 , 18 ], who have described the male predominance of mean age 31–33.2 years in their works.…”
Section: Discussioncontrasting
confidence: 99%
“…Research also reported that hydatid cystic rupture may be spontaneous in young people who have a history of frequent trauma (10). Despite no known history of trauma in the present case, the diagnosis was spontaneous rupture, as the event developed during sporting activities.…”
Section: Discussionmentioning
confidence: 99%
“…Hydatid pulmonary embolism is a rare but potentially life-threatening complication due to the risk of acute fatal complications such as anaphylactic shock (5). It is reported that the incidence of sudden death due to hydatid cyst is around 1.1-1.3% (6,7). It is difficult to explain the involvement of a hydatid cyst in the death mechanism, particularly if it is seen intact and discovered at autopsy (8).…”
Section: Introductionmentioning
confidence: 99%